Effect of 0.05% topical cyclosporine for the treatment of symptomatic subepithelial infiltrates due to adenoviral keratoconjunctivitis - Ilkay Kilic Muftuoglu; Yonca A. Akova; Sirel G. Gungor (International Journal of Ophthalmology, 2016)
Letter to the editor